Photoelectrochemical water splitting materials, processes and architectures - Lewerenz, H.- J.; Peter, Laurence (Laurence M.) (RSC energy and environment series, 2013)
There has been a resurgence of interest in light-induced water splitting as the search for storable carbon neutral energy becomes more urgent. Although the history of the basic idea dates back more than four decades, efficient, economical and stable integrated devices have yet to be realized. In the continuing quest for such devices, the field of photoelectrochemistry is entering a new phase where the extraordinary interdisciplinary of the research and development efforts are opening new avenues. This aspect of current research effort is reflected in the chapters of this book, which encompass present thinking in the various disciplines such as materials science, photo-electrochemistry and interfaces that can contribute to realization of viable solar fuel generators. This book presents a blend of the background science and recent advances in the field of photoelectrochemical water splitting, and includes aspects that point towards medium to long term future realization. The content of the book goes beyond the more traditional approaches to the subject by including topics such as novel excitation energy processes that have only been realized so far in advanced photonics. The comprehensive overview of current activities and development horizons provided by the impressive collection of internationally renowned authors therefore represents a unique reflection of current thinking regarding water splitting by light.